2015
DOI: 10.5858/arpa.2014-0127-oa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HER2/neu Status by Immunohistochemistry Using Computer-Based Image Analysis and Correlation With Gene Amplification by Fluorescence In Situ Hybridization Assay: A 10-Year Experience and Impact of Test Standardization on Concordance Rate

Abstract: College of American Pathologists proposed several recommendations for human epidermal growth factor receptor 2 (HER2) test standardization. One suggestion was that image analysis (IA) could be useful for scoring of HER2/ neu immunohistochemistry. The utilization of IA in a realworld practice in a large cohort of cases has not been previously reported.Objectives.-To compare HER2/neu quantification by IA with gene amplification by fluorescence in situ hybridization (FISH); to determine sensitivity, specificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…6,13 A local study and studies from America, Iran, and Saudi Arabia reported concordance rate of 74%, 69%, 61.5% and 50%, respectively. 8,14,16,19 A Turkish study reported amplification in 75% in IHC 3+ cases which is contrary to the present results. 7 Most of the studies including the present one showed an overall high concordance between IHC3+/FISH amplified and IHC negative/FISH non-amplified groups.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…6,13 A local study and studies from America, Iran, and Saudi Arabia reported concordance rate of 74%, 69%, 61.5% and 50%, respectively. 8,14,16,19 A Turkish study reported amplification in 75% in IHC 3+ cases which is contrary to the present results. 7 Most of the studies including the present one showed an overall high concordance between IHC3+/FISH amplified and IHC negative/FISH non-amplified groups.…”
Section: Discussioncontrasting
confidence: 97%
“…7,[12][13][14] Studies from Switzerland and USA reported 99%, 95% concordance and 1%, 2% discordance between Her-2/neu FISH and Her-2/neu IHC in cases showing negative immunohistochemistry. 15,16 Other studies from Turkey, India, and Saudi Arabia reported concordance of 80%, 85%, 87% and 84% in cases with negative immunostaining and Her-2/neu FISH, respectively. 3 These frequencies are slightly lower than the present findings, which may be possibly due to sample size difference.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The concordance level found between the IHC testing performed at the treating institution and FACS and RT-q-PCR testing for IHC 0 and 1+ tumors was consistent with a number of studies evaluating the concordance between IHC results and FISH amplification status (~99%). However, concordance between IHC and FISH results are lower for IHC 2+ results (~90%–95%) and even lower for IHC 3+ results (~85%) suggesting the potential need for improved methods of evaluating HER2 receptor status [1921]. New HER2 mRNA quantification methods are emerging that may offer improved specificity or sensitivity than IHC or FISH methods [22].…”
Section: Discussionmentioning
confidence: 99%
“…The discordance rate observed in our study is probably due to a lack of standardization in tissue processing (i.e., CIT and fixation conditions). Other authors reported higher concordance rates that were related to improved specimen handling, test standardization, and experience in the interpretation of HER-2 IHC [24].…”
Section: Discussionmentioning
confidence: 98%